Illocutionary Acts Uttered by Ralph in Film Wreck-It Ralph - Vania Myanti, Ayu Putu (Udayana Journal of Social Sciences and Humanities, 2020)
This study focused on the discussion of illocutionary acts uttered by the main character. This study aims to identify the functions and the illocutionary acts force uttered by Ralph in the film „Wreck-It Ralph?. The data were taken from a film entitled Wreck-It Ralph and its dialogue transcript. The expressions of the character when they talk to each other can be seen clearly by watching the film, while the conversations between characters can be easily understood by reading the dialogue transcript. The theory used in this study is proposed by Yule (1996). This study used a qualitative method. The steps to analyze the data were categorizing the illocutionary acts uttered by Ralph, analyzing the illocutionary acts uttered by Ralph, and then writing the result as a thesis. The result of the study showed that there were four types of functions and seventeen types of forces uttered by Ralph in film Wreck-It Ralph. The illocutionary act functions uttered by Ralph are representative with asserting, concluding, describing forces; expressive with protesting, disliking, congratulating, complaining, apologizing, joy forces; directive requesting, asking, commanding, advising, suggesting forces and commissive with swearing, refusing, and promising forces.